National hepatitis registry in Pakistan: a dire need for hepatitis surveillance and control - Muhammad Farhan; Faizan Fazal; Tirth Dave; Armeen Butt; Jawad Basit; Shahzaib Maqbool (Tropical Medicine and Health, 2023)
Abstract Hepatitis is a major public health issue in Pakistan, with an estimated 11.55% prevalence of HCV infection in the adult population. The country ranks second globally in terms of hepatitis C virus (HCV) infections, with approximately one in every 20 Pakistanis already infected. The mortality rates due to HBV and HCV stand at 563,000 and 366,000 annually, respectively. However, the absence of a national registry or database system and the lack of coordination among provinces pose significant obstacles in combating this disease effectively. To address this issue, the establishment of a centralized national database registry is crucial, allowing comprehensive analysis, tracking of hepatitis prevalence, and identification of high-risk areas for targeted interventions. By fostering collaboration among provinces, the government, and non-governmental organizations, the registry would facilitate joint decision-making, minimize duplication of efforts, and address inconsistencies in diagnosis and treatment. Collaborating with student-run organizations and leveraging enhanced laboratory capacities post-COVID era can strengthen the hepatitis control program. The centralized approach and unified efforts are necessary to achieve the goal of a hepatitis-free Pakistan, where a healthier future can be realized.